Characterization and treatment of natural organic matter from raw water supply reservoir in Thailand - Suksaroj, Chaisri; Chaimongkol, Phantipa; Wattanachira, Suraphong; Musikavong, Charongpun (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this paper is to review the characteristic of natural organic matter (NOM) in raw water supply reservoir in Thailand. The dissolved organic carbon (DOC), ultraviolet absorption at wavelength 254 nm (UV-254), specific ultraviolet absorption (SUVA), trihalomethane formation potential (THMFP), hydrophobic organic fraction (HPO), hydrophilic organic fraction (HPI) and fluorescent excitation emission matrix (FEEM) were utilized to represent the nature of NOM from six reservoir including Mae-Hia Reservoir, Aung-Keaw Reservoir, Mae-Kuang Reservoir in Chiang Mai province, the Bhumibol Dam reservoir in Tak province, the Northern-Region Industrial Estate Reservoir in Lamphun province, and Sri-Trang Reservoir in Songkhla province. In addition, the removal of NOM in raw water supply from six reservoirs by coagulation was also summarized. The collected data show that the major group of organic matter found in reservoir water is humic acid and fulvic acid like substances, DOC values were less than 5 mg/L and UV- 254 in all samples were less than 0.3. The alum coagulation that was used in conventional water treatment plant seems to be used effectively in objective of NOM removal also. This method is convenient and has low operation cost and showed the appreciatory value of organic removal in term of UV-254 compared with DOC in comparable to coagulation with FeCl3 . The contact flocculation filtration using alum as coagulant could reduce NOM less than that operated with jar test.